The nomadic object : the challenge of world for early modern religious art - Göttler, Christine; Mochizuki, Mia M. (Intersections (Boston, Mass.), 2018)
At the turn of the sixteenth century, the notion of world was dramatically being reshaped, leaving no aspect of human experience untouched. The Nomadic Object: The Challenge of World for Early Modern Religious Art examines how sacred art and artefacts responded to the demands of a world stage in the age of reform. Essays by leading scholars explore how religious objects resulting from cross-cultural contact defied national and confessional categories and were re-contextualised in a global framework via their collection, exchange, production, management, and circulation. In dialogue with current discourses, papers address issues of idolatry, translation, materiality, value, and the agency of networks. The Nomadic Object demonstrates the significance of religious systems, from overseas logistics to philosophical underpinnings, for a global art history.--